Chernets M.V. To the question about the calculation of limits the changes of the teeth gearing in cylindrical obliquely teeth transmissions of and its influence on pin pressures. - Чернець, М.В. (Problems of Tribology, 2016)
The paper presents the results undertaken the using of methodology of calculation the corners that is determined by the limits of the gearing the teeth pairs correction in cylindrical transmissions. Considered the cases of two-one pairs teeth, three-two pairs teeth, four-three pairs teeth gearing. The analysis of influence to gearing the teeth pairs on a size and charac-ter of change the maximal contact pressures was conducted .Key words: cylindrical gearing , limits of gearing changes , two-one pairs teeth, three-two pairs teeth, four-three pairs teeth gearing, maximum contact pressure